Diaphragm and preparation method and application thereof
By using NASICON type lithium-ion solid electrolytes including at least four tetravalent metal elements in the battery separator, the hydrolysis problem caused by water absorption in a low dew point environment is solved, high ionic conductivity and low water absorption are achieved, and the safety and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN202410932578.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2025-04-15
AI Technical Summary
The traditional NASICON type lithium-ion solid electrolyte absorbs moisture in a low dew point environment and leads to hydrolysis, reducing the reliability and conductivity of the battery separator. The vacuum baking will destroy the stability of the separator and increase production costs.
Using a NASICON type lithium ion solid electrolyte including at least four tetravalent metal elements, a NASICON type lithium ion solid electrolyte is obtained by mixing and sintering the metal element source, a lithium source and a phosphorus source, and mixing it with a solvent to form a coating slurry, and coating it on the base film to form a separator.
It improves the ionic conductivity of the separator, reduces water absorption, enhances the safety and electrochemical performance of the battery, reduces production costs, and is suitable for industrial applications.
Smart Images

Figure CN119833887A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a diaphragm and a preparation method and application thereof. Background Art
[0002] At present, sodium superion conductor (NASICON) type lithium ion solid electrolyte can be coated in the battery diaphragm to improve the electrochemical performance of the battery because of its low price, high ionic conductivity and high stability. Although the traditional NASICON type lithium ion solid electrolyte can exist stably in an air environment, it has a strong affinity for water and absorbs a large amount of water in a low dew point environment, causing the NASICON type lithium ion solid electrolyte to hydrolyze, and the reliability and conductivity of the battery diaphragm are reduced. In the related art, the moisture in the NASICON type lithium ion solid electrolyte can be removed by vacuum baking, but vacuum baking will destroy the stability of the diaphragm, aggravate the battery discharge phenomenon, cause the battery short circuit, and increase the production cost, which is not conducive to industrial production. Therefore, a diaphragm with low water absorption and high ionic conductivity is needed. Summary of the invention
[0003] In view of this, the present application provides a diaphragm and a preparation method and application thereof. The diaphragm has a NASICON-type lithium-ion solid electrolyte. The NASICON-type lithium-ion solid electrolyte has a tetravalent metal element, which improves the ionic conductivity of the diaphragm and reduces the water absorption of the diaphragm, which is beneficial to improving the safety performance and electrochemical performance of the battery.
[0004] In a first aspect, the present application provides a diaphragm, comprising a base membrane and a coating layer disposed on at least one surface of the base membrane, the diaphragm comprising a base membrane and a coating layer disposed on at least one surface of the base membrane, the coating layer comprising a NASICON-type lithium-ion solid electrolyte, the chemical formula of the NASICON-type lithium-ion solid electrolyte being LiM2(PO4)3, wherein M is at least four tetravalent metal elements.
[0005] Optionally, the metal element is selected from Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn.
[0006] Optionally, among the at least four tetravalent metal elements, the molar percentage of each of the metal elements is greater than or equal to 10%.
[0007] Optionally, the metal elements are Ti, Ge, Sn, Zr and Hf.
[0008] Optionally, the chemical formula of the NASICON type lithium ion solid electrolyte includes LiTi 0.4 Zr 0.4 Hf 0.4 Sn0.4 Ge 0.4 (PO4)3、LiTi 0.8 Hf 0.4 Sn 0.4 Ge 0.4 (PO4)3、LiCe 0.5 Zr 0.4 Ge 0.5 Hf 0.5 (PO4)3、LiTi 0.5 Zr 0.5 Pb 0.5 Ce 0.5 (PO4)3 and LiTi 1.4 Hf 0.2 Sn 0.2 Ge 0.2 (PO4)3 or more.
[0009] Optionally, the configuration entropy of the NASICON lithium-ion solid electrolyte is greater than or equal to 10.73 J / (mol·K).
[0010] Optionally, the particle size of the NASICON-type lithium-ion solid electrolyte is greater than or equal to the pore size of the base membrane.
[0011] Optionally, the D50 particle size of the NASICON lithium-ion solid electrolyte is 0.5 μm-1.5 μm, and the pore size of the base membrane is 0.7 μm-1.2 μm.
[0012] Optionally, the base film has a thickness of 7 μm-20 μm, and the coating layer has a thickness of 0.5 μm-5 μm.
[0013] Optionally, the ionic conductivity of the NASICON type lithium ion solid electrolyte is greater than or equal to 0.1 mS / cm, and the water absorption per gram of the NASICON type lithium ion solid electrolyte is less than or equal to 0.2 wt %.
[0014] Optionally, the ionic conductivity of the membrane is greater than or equal to 0.9 mS / cm, and the water absorption per gram of the membrane is less than or equal to 0.19 wt%.
[0015] The diaphragm provided in the present application is coated with a NASICON type lithium ion solid electrolyte, which has a tetravalent metal element, improves the ionic conductivity of the diaphragm and reduces the water absorption of the diaphragm.
[0016] In a second aspect, the present application provides a method for preparing a diaphragm, comprising:
[0017] The metal element source, the lithium source and the phosphorus source are mixed and sintered to obtain a NASICON type lithium ion solid electrolyte;
[0018] The NASICON type lithium ion solid electrolyte is mixed with a solvent to obtain a coating slurry, and the coating slurry is disposed on at least one side of a base film to form a coating layer to obtain a separator.
[0019] Optionally, the molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source and the metal element in the metal element source is (0.33-0.5):(1.4-1.6):1.
[0020] Optionally, the metal element source includes one or more of metal nitrates, metal organic salts and metal oxides.
[0021] Optionally, the solid content of the coating slurry is 20%-40%.
[0022] Optionally, the sintering temperature is 700°C-1000°C.
[0023] The preparation method of the diaphragm provided in the present application is novel, the preparation process is simple, the preparation cost is low, and the prepared product has excellent performance.
[0024] In a third aspect, the present application provides a battery, wherein the battery comprises the diaphragm described in the first aspect or the diaphragm prepared by the preparation method described in the second aspect.
[0025] The battery provided in the present application has a long cycle life and good electrochemical performance, and is conducive to industrial application.
[0026] In a fourth aspect, the present application provides an electrical device, wherein the electrical device comprises the battery described in the third aspect.
[0027] The electrical equipment provided in this application has excellent comprehensive performance, greatly improved safety performance, and strong product competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the embodiments or the prior art description. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0029] Figure 1 A schematic diagram of the cross-sectional structure of a diaphragm provided in one embodiment of the present application;
[0030] Figure 2 A flow chart of a method for preparing a diaphragm provided in one embodiment of the present application;
[0031] Figure 3 X-ray diffraction spectra of NASICON lithium-ion solid electrolytes prepared in Examples 1-4 and Comparative Examples 1-2 of the present application;
[0032] Figure 4 This is the electrochemical impedance spectrum of the NASICON lithium-ion solid electrolyte sheet prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0034] In the related art, conventional sodium superion structure (NASICON) type lithium ion solid electrolytes (such as LATP and LAGP) have two or more metal elements, such as Al, Ti and Ge. A small amount of Al is doped in LATP and LAGP. In the crystal structure, Al 3+ Occupies Ti 4+ Or Ge 4+ sites, resulting in lattice expansion and charge imbalance. In order to balance the crystal charge, additional Li + , improve the structural stability of NASICON lithium-ion solid electrolyte; Li + The entry of lithium ions increases the ion diffusion channels of lithium ions, thereby greatly improving the ionic conductivity of the NASICON lithium-ion solid electrolyte; however, the additional lithium ions will increase the affinity of the NASICON lithium-ion solid electrolyte for water, reduce the stability of the NASICON lithium-ion solid electrolyte to water, and are not conducive to the preparation, storage and transportation of the NASICON lithium-ion solid electrolyte. When used in battery separators, the water absorption of the separator is increased, the stability of the separator is reduced, and it is not conducive to improving the electrochemical performance and cycle life of the battery; the moisture in the NASICON lithium-ion solid electrolyte can be removed by vacuum baking, but vacuum baking will destroy the stability of the separator, aggravate the battery discharge phenomenon, cause battery short circuit, and increase the production cost, which is not conducive to industrial production.
[0035] See also Figure 1, is a schematic diagram of the cross-sectional structure of a diaphragm provided in one embodiment of the present application, wherein the diaphragm 100 comprises a base film 11 and a coating layer 12 disposed on at least one side of the base film 11, wherein the coating layer 12 comprises a NASICON type lithium ion solid electrolyte, wherein the chemical formula of the NASICON type lithium ion solid electrolyte is LiM2(PO4)3, wherein M is at least four tetravalent metal elements. The diaphragm provided in the present application comprises a coating layer, wherein the coating layer comprises a NASICON type lithium ion solid electrolyte, wherein the NASICON type lithium ion solid electrolyte has high air stability and is beneficial to the preparation, storage and transportation of the diaphragm; and at least four tetravalent metal elements are used as metal elements, which not only improves the ionic conductivity of the NASICON type lithium ion solid electrolyte, but also avoids the introduction of excessive lithium atoms due to charge imbalance caused by different charges of metal elements, reduces the affinity of the NASICON type lithium ion solid electrolyte to water, avoids the removal of moisture in the NASICON type lithium ion solid electrolyte by vacuum baking, etc., improves the ionic conductivity and reliability of the diaphragm, reduces the water absorption and preparation cost of the diaphragm, and is beneficial to the industrial application of the diaphragm.
[0036] In the present application, the base film 11 can improve the mechanical strength of the diaphragm 100 and extend the service life of the diaphragm 100. Specifically, the material of the base film 11 can be, but is not limited to, one or more of polyethylene, polypropylene, polyvinylidene fluoride and polyimide. In one embodiment of the present application, the material of the base film 11 can be polyethylene. In another embodiment of the present application, the material of the base film 11 can be polypropylene. In another embodiment of the present application, the material of the base film 11 can be a composite diaphragm of polyethylene and polypropylene.
[0037] In one embodiment of the present application, the thickness of the base film 11 is 7μm-20μm. The appropriate thickness of the base film 11 can maintain high mechanical strength while improving the ionic conductivity of the base film 11 and the electrochemical performance of the battery. Specifically, the thickness of the base film 11 can be, but not limited to, 7μm, 10μm, 12μm, 15μm, 18μm or 20μm, etc. In one embodiment of the present application, the thickness of the base film 11 can be 7μm-15μm. In another embodiment of the present application, the thickness of the base film 11 can be, but not limited to, 10μm-20μm.
[0038] In one embodiment of the present application, the pore size of the base film 11 is 0.7 μm-1.2 μm, and the appropriate pore size of the base film 11 is conducive to improving the ionic conductivity of the diaphragm 100. Specifically, the pore size of the base film 11 can be, but is not limited to, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm or 1.2 μm, etc. In one embodiment of the present application, the pore size of the base film 11 can be 0.7 μm-1 μm. In another embodiment of the present application, the pore size of the base film 11 can be 1 μm-1.2 μm.
[0039] In the present application, the coating layer 12 includes a NASICON type lithium ion solid electrolyte, which can improve the ionic conductivity of the separator 100, reduce the water absorption of the separator 100, and further improve the cycle life of the battery.
[0040] In one embodiment of the present application, the thickness of the coating layer 12 is 0.5 μm-5 μm. The appropriate thickness of the coating layer 12 can not only ensure that the diaphragm has a high structural stability, but also maintain the diaphragm with a high ion pass rate and low water absorption, which is beneficial to improve the electrochemical performance of the diaphragm 100. Specifically, the thickness of the coating layer 12 can be, but is not limited to, 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm. In one embodiment of the present application, the thickness of the coating layer 12 can be 0.5 μm-3 μm. In another embodiment of the present application, the thickness of the coating layer 12 can be 2.5 μm-5 μm.
[0041] In the present application, the chemical formula of the NASICON type lithium ion solid electrolyte is LiM2(PO4)3, where M is at least four tetravalent metal elements. The tetravalent metal elements can improve the ionic conductivity of the NASICON type lithium ion solid electrolyte, while avoiding the introduction of additional lithium atoms due to charge imbalance, thereby reducing the affinity of the NASICON type lithium ion solid electrolyte for water. Specifically, the metal element can be, but is not limited to, selected from Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn. In one embodiment of the present application, the metal element may be Ti, Ge, Mn and V. In another embodiment of the present application, the metal element may be Ti, Ge, Sn, Zr and Hf, which can further improve the ionic conductivity of the NASICON type lithium ion solid electrolyte and reduce its water absorption.
[0042] In one embodiment of the present application, among the at least four tetravalent metal elements, the molar percentage of each metal element is greater than or equal to 10%. In some embodiments, when the NASICON type lithium ion solid electrolyte has four metal elements, the four metal elements can be in an equal molar ratio, the molar percentage of each metal element is 25%, and the molar number of each metal element is 0.5. In this case, the chemical formula of the NASICON type lithium ion solid electrolyte can be LiTi 0.5 Zr 0.5 Mn 0.5 Sn 0.5(PO4)3. In some other embodiments, when the NASICON type lithium ion solid electrolyte has four metal elements, the four metal elements may be in non-equivalent molar ratios, the minimum molar percentage of each metal element is greater than or equal to 10%, the molar percentage of the metal element may be 10%, 15%, 20%, 30% or 35%, etc., the molar number of the metal element may be 0.3, 0.4, 0.6 and 0.7, and the chemical formula of the NASICON type lithium ion solid electrolyte may be LiTi 0.3 Zr 0.4 Mn 0.6 Sn 0.7 (PO4)3. In some other embodiments, the metal elements may be Ti, Ge, Sn, Zr and Hf, and the five metal elements may be in non-equimolar ratios. The chemical formula of the NASICON lithium-ion solid electrolyte is LiTi 0.4 Zr 0.4 Hf 0.4 Sn 0.4 Ge 0.4 (PO4)3 can further improve the ionic conductivity of NASICON-type lithium-ion solid electrolyte and reduce its water absorption.
[0043] In one embodiment of the present application, the configuration entropy of the NASICON lithium-ion solid electrolyte is greater than or equal to 10.73 J / (mol·K). The calculation formula for the configuration entropy is: Where R is 8.314, N is the number of metal elements in the NASICON lithium-ion solid electrolyte, and x i is the molar percentage of a certain metal element, x i Greater than or equal to 10%. Specifically, the configuration entropy of the NASICON lithium-ion solid electrolyte may be, but is not limited to, greater than or equal to 10.73 J / (mol·K), greater than or equal to 10.8 J / (mol·K), greater than or equal to 10.9 J / (mol·K), greater than or equal to 11 J / (mol·K), greater than or equal to 11.2 J / (mol·K), greater than or equal to 11.4 J / (mol·K), or greater than or equal to 11.5 J / (mol·K), etc. In one embodiment of the present application, the configuration entropy of the NASICON lithium-ion solid electrolyte may be greater than or equal to 11 J / (mol·K). In another embodiment of the present application, the configuration entropy of the NASICON lithium-ion solid electrolyte may be greater than or equal to 11.2 J / (mol·K).
[0044] In one embodiment of the present application, the ionic conductivity of the NASICON type lithium ion solid electrolyte is greater than or equal to 0.1mS / cm, which is beneficial to improve the ionic conductivity of the diaphragm 100, reduce the internal resistance of the battery, and is beneficial to improve the rate performance and cycle performance of the battery. Specifically, the ionic conductivity of the NASICON type lithium ion solid electrolyte may be, but is not limited to, greater than or equal to 0.1mS / cm, greater than or equal to 0.2mS / cm, greater than or equal to 0.5mS / cm, greater than or equal to 0.65mS / cm, greater than or equal to 0.7mS / cm, or greater than or equal to 0.75mS / cm, etc. In one embodiment of the present application, the ionic conductivity of the NASICON type lithium ion solid electrolyte may be greater than or equal to 0.65mS / cm. In another embodiment of the present application, the ionic conductivity of the NASICON type lithium ion solid electrolyte may be greater than or equal to 0.7mS / cm.
[0045] In one embodiment of the present application, the water absorption of each gram of NASICON lithium ion solid electrolyte is less than or equal to 0.2wt%. The water absorption of NASICON lithium ion solid electrolyte is small, which improves the stability of the diaphragm 100 and reduces the preparation cost of the battery. Specifically, the water absorption of each gram of NASICON lithium ion solid electrolyte can be, but is not limited to, less than or equal to 0.2wt%, less than or equal to 0.18wt%, less than or equal to 0.17wt%, less than or equal to 0.15wt% or less than or equal to 0.13wt%, etc. In one embodiment of the present application, the water absorption of each gram of NASICON lithium ion solid electrolyte can be less than or equal to 0.19wt%. In another embodiment of the present application, the water absorption of each gram of NASICON lithium ion solid electrolyte can be less than or equal to 0.16wt%.
[0046] In one embodiment of the present application, the D50 particle size of the NASICON type lithium ion solid electrolyte is larger than the pore size of the base film 11, and the D50 particle size of the NASICON type lithium ion solid electrolyte is 0.5μm-1.5μm. The appropriate D50 particle size of the NASICON type lithium ion solid electrolyte can further improve the ionic conductivity of the NASICON type lithium ion solid electrolyte. Specifically, the D50 particle size of the NASICON type lithium ion solid electrolyte can be, but is not limited to, 0.5μm, 0.8μm, 0.9μm, 1μm, 1.2μm, 1.4μm or 1.5μm, etc. In one embodiment of the present application, the D50 particle size of the NASICON type lithium ion solid electrolyte can be 0.5μm-1.2μm. In another embodiment of the present application, the D50 particle size of the NASICON type lithium ion solid electrolyte can be 1μm-1.5μm.
[0047] In one embodiment of the present application, the coating layer 12 also includes a binder, which can improve the bonding force between the coating layer 12 and the base film 11 and enhance the mechanical strength of the diaphragm 100. Specifically, the binder may include, but is not limited to, one or more of styrene-butadiene rubber, water-soluble unsaturated resin SR-1B, sodium alginate, polyurethane, polyacrylic acid, polyethyl acrylate, polymethacrylic acid, sodium polyacrylate, sodium polycarboxymethyl cellulose, acrylamide, polyvinyl alcohol, and carboxymethyl chitosan. In one embodiment of the present application, the binder may be styrene-butadiene rubber. In another embodiment of the present application, the binder may be polyacrylic acid.
[0048] In one embodiment of the present application, the ionic conductivity of the diaphragm 100 is greater than or equal to 0.9mS / cm, which is beneficial to improving the electrochemical performance of the battery. Specifically, the ionic conductivity of the diaphragm 100 may be, but is not limited to, greater than or equal to 0.9mS / cm, greater than or equal to 0.95mS / cm, greater than or equal to 1mS / cm, greater than or equal to 1.1mS / cm, greater than or equal to 1.2mS / cm, or greater than or equal to 1.4mS / cm, etc. In one embodiment of the present application, the ionic conductivity of the diaphragm 100 may be greater than or equal to 1mS / cm. In another embodiment of the present application, the ionic conductivity of the diaphragm 100 may be greater than or equal to 1.2mS / cm.
[0049] In one embodiment of the present application, the water absorption of each gram of the diaphragm 100 is less than or equal to 0.19wt%. The small water absorption of the diaphragm 100 improves the cycle life of the battery and reduces the preparation, storage and transportation costs of the battery. Specifically, the water absorption of each gram of the diaphragm 100 may be, but is not limited to, less than or equal to 0.19wt%, less than or equal to 0.18wt%, less than or equal to 0.17wt%, less than or equal to 0.15wt%, or less than or equal to 0.13wt%, etc. In one embodiment of the present application, the water absorption of each gram of the diaphragm 100 may be less than or equal to 0.19wt%. In another embodiment of the present application, the water absorption of each gram of the diaphragm 100 may be less than or equal to 0.16wt%.
[0050] In one embodiment of the present application, NASICON-type lithium-ion solid electrolyte can also be used in electrolytes and positive electrode plates to improve the ionic conductivity and structural stability of the battery.
[0051] See also Figure 2 , a method for preparing a diaphragm provided in one embodiment of the present application, comprising:
[0052] S101: mixing a metal element source, a lithium source and a phosphorus source, and sintering to obtain a NASICON type lithium ion solid electrolyte;
[0053] S102: Mixing a NASICON lithium-ion solid electrolyte with a solvent to obtain a coating slurry, and placing the coating slurry on at least one side of the base film to form a coating layer to obtain a diaphragm. The preparation method provided by the present application is novel, the preparation process is simple, the preparation cost is low, and the prepared diaphragm has high ion conductivity and low water absorption, which is conducive to improving the cycle life and electrochemical performance of the battery.
[0054] In one embodiment of the present application, the metal element source includes one or more of metal nitrates, metal organic salts and metal oxides. Specifically, the metal nitrate may include, but is not limited to, one or more of zirconium nitrate (Zr(NO3)4·5H2O), cerium nitrate (Ce(NO3)4·5H2O), manganese nitrate (Mn(NO3)4), tin nitrate (Sn(NO3)4), molybdenum nitrate (Mo(NO3)4) and lead nitrate (Pb(NO3)4); the metal organic salt may include, but is not limited to, one or more of metal organic alkoxides; the metal oxide may include, but is not limited to, one or more of TiO2, GeO2, MnO2, VO2, HfO2, SnO2 and PbO2. In one embodiment of the present application, when a NASICON type lithium ion solid electrolyte is prepared by a solid phase method, the metal element source may be a metal oxide. In another embodiment of the present application, when a NASICON type lithium ion solid electrolyte is prepared by a liquid phase method, the metal element source may be a metal nitrate and a metal organic salt.
[0055] In one embodiment of the present application, the lithium source provides lithium elements to form a NASICON type lithium ion solid electrolyte, which is beneficial to improve the conductivity of the electrolyte. Specifically, the lithium source may include, but is not limited to, one or more of LiOH·H2O, Li2CO3 and LiNO3. In one embodiment of the present application, the lithium source may be Li2CO3. In another embodiment of the present application, the lithium source may be LiNO3.
[0056] In one embodiment of the present application, the phosphorus source may include, but is not limited to, one or more of NH4H2PO4, H3PO4, and (NH4)2HPO4. Specifically, the phosphorus source may be NH4H2PO4. In another embodiment of the present application, the phosphorus source may be (NH4)2HPO4 and H3PO4.
[0057] In one embodiment of the present application, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source is (0.33-0.5):(1.4-1.6):1. Specifically, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source may be, but is not limited to, 0.33:1.4:1, 0.4.2:1.42:1, 0.45:1.45:1, 0.48:1.48:1, 0.45:1.5:1, 0.48:1.55:1, or 0.5:1.6:1, etc. In one embodiment of the present application, the molar ratio of lithium in the lithium source, phosphorus in the phosphorus source, and metal in the metal source may be (0.33-0.45):(1.4-1.55):1. In another embodiment of the present application, the molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source, and the metal element in the metal element source can be (0.44-0.5):(1.5-1.6):1.
[0058] In one embodiment of the present application, a NASICON type lithium ion solid electrolyte is prepared by a solid phase method, wherein the metal element source can be a metal oxide, the lithium source can be a Li2CO3 solution, and the phosphorus source can be a (NH4)2HPO4 solution. The metal oxide weighed according to the stoichiometric ratio is ground, and the phosphorus source is added to form a mixed solution; the lithium source is added to the mixed solution, dried at 180°C, and sintered to obtain a NASICON type lithium ion solid electrolyte.
[0059] In one embodiment of the present application, the metal oxides are proportioned according to a stoichiometric ratio, and the grinding time is 1h-6h. The metal oxides can be proportioned according to an equimolar ratio or a non-equimolar ratio. When the metal oxides are proportioned in a non-equimolar ratio, the molar percentage of each metal oxide is greater than or equal to 10% in terms of the metal oxide. Specifically, the grinding time can be, but is not limited to, 1h, 2h, 3h, 4h, 5h or 6h, etc. In one embodiment of the present application, the grinding time can be 1h-4h. In another embodiment of the present application, the grinding time can be 3h-6h. In some embodiments, zirconium oxide balls and / or aluminum oxide balls are added during grinding.
[0060] In one embodiment of the present application, a liquid phase method is used to prepare a NASICON type lithium ion solid electrolyte, wherein the metal element source can be a metal organic alkoxide and a metal nitrate, the lithium source can be LiNO3, and the phosphorus source can be (NH4)2HPO4. The metal nitrate weighed in a stoichiometric ratio is added to water to form a metal nitrate solution; the lithium source and the phosphorus source are mixed, and water is added to form a lithium source-phosphorus source mixed solution; the metal organic alkoxide is added to ethanol to form a metal organic alkoxide solution; the metal nitrate solution, the lithium source-phosphorus source mixed solution and the metal organic alkoxide solution are uniformly mixed, dried at 120°C, and sintered to obtain a NASICON type lithium ion solid electrolyte.
[0061] In one embodiment of the present application, the structural formula of the metal organic alkoxide is M'(OR)4, R is -(CH2) a CH3, the value of a is 0-6. Specifically, M' can be but not limited to Ti, Ge or V, and the value of a can be but not limited to 0, 1, 2, 3, 4, 5 or 6. In one embodiment of the present application, when M' is Ti and a is 2, the metal organic alkoxide can be Ti(O(CH2)2CH3)4. In another embodiment of the present application, when M' is Ge and a is 4, the metal organic alkoxide can be Ge(O(CH2)4CH3)4.
[0062] In one embodiment of the present application, the solid content of the coating slurry is 20%-40%, which can improve the uniformity of the coating layer. Specifically, the solid content of the coating slurry can be, but is not limited to, 20%, 25%, 30%, 35% or 40%. In one embodiment of the present application, the solid content of the coating slurry can be 20%-30%. In another embodiment of the present application, the solid content of the coating slurry can be 30%-40%.
[0063] In one embodiment of the present application, the solvent of the coating slurry can promote the uniform dispersion of the components in the coating slurry and improve the uniformity of the coating layer. Specifically, the solvent can be, but is not limited to, one or more of water, N-methylpyrrolidone, ethanol and acetonitrile. In one embodiment of the present application, the solvent can be water. In another embodiment of the present application, the solvent can be ethanol.
[0064] In one embodiment of the present application, the sintering temperature is 700°C-1000°C, and a suitable sintering temperature can promote the formation of NASICON type lithium ion solid electrolyte. Specifically, the sintering temperature can be, but is not limited to, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C. In one embodiment of the present application, the sintering temperature is 700°C-900°C. In another embodiment of the present application, the sintering temperature is 850°C-1000°C. In some embodiments, the sintering atmosphere is air, an inert gas or oxygen.
[0065] The present application provides a battery, comprising a diaphragm provided by any of the above embodiments or a diaphragm prepared by the preparation method provided by any of the above embodiments. The diaphragm provided by the present application has high ion conductivity and low water absorption, which is conducive to improving the electrochemical performance and cycle life of the battery.
[0066] In one embodiment of the present application, the battery includes a positive electrode sheet and a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet. In one embodiment of the present application, the battery also includes an electrolyte. Among them, at least part of the positive electrode sheet and at least part of the negative electrode sheet are immersed in the electrolyte. The electrolyte of the present application is not particularly limited, and can be, but not limited to, various substances that can be used as battery electrolytes in the art.
[0067] The present application also provides an electrical device, which includes the battery described in any of the above embodiments. The electrical device provided by the present application has good cycle performance, high safety performance, and strong market competitiveness. Electrical equipment includes vehicles, electronic equipment, energy storage systems, etc., wherein the electronic equipment may include, for example, mobile phones, tablets, watches, VR glasses, etc. In one embodiment of the present application, the battery can be used in vehicles, which can increase the service life and charging rate of the vehicle, increase the widespread application of new energy vehicles, and facilitate the construction of a green and environmentally friendly environment. In another embodiment of the present application, the battery can also be used in mobile phones, which can reduce the preparation cost of the battery and improve the safety of battery use. The above-mentioned battery of the present application can be arranged in the electrical equipment in the form of a single cell, a battery module, a battery pack, etc.
[0068] The effect of the technical solution of the present application is further illustrated below through specific examples.
[0069] Example 1
[0070] 500 g of a metal element source (TiO2, HfO2, SnO2 and GeO2 in a molar ratio of 2:1:1:1) was ground using a 6 mm zirconia ball for 6 h to obtain a ground metal element source;
[0071] Dissolve 160 g of a lithium source (Li2CO3) in 200 ml of water to form a lithium source solution, wherein the molar ratio of the lithium element in the lithium source to the metal element in the metal element source is 0.45:1;
[0072] 690 g of phosphorus source (NH4H2PO4), ground metal element source and lithium source solution were mixed, dried at 180°C for 12 h, and sintered at 950°C in air atmosphere to obtain NASICON type lithium ion solid electrolyte, wherein the molar ratio of phosphorus element in the phosphorus source to metal element in the metal element source was 3:2;
[0073] The NASICON type lithium ion solid electrolyte was crushed to a D50 of 500 nm, dissolved in N-methylpyrrolidone to form a coating slurry with a solid content of 25%, and coated on a 9 μm polyethylene base film with a coating layer thickness of 2 μm to obtain a separator;
[0074] The positive electrode sheet (the positive electrode active material is 811 lithium nickel cobalt manganese oxide), the negative electrode sheet (the negative electrode active material is graphite), the electrolyte (LiPF6 with a lithium salt concentration of 1M, and the solvent is EC, DMC, DEC with a volume ratio of 1:1:1) and the separator are assembled to produce a soft-pack battery.
[0075] Example 2
[0076] The difference from Example 1 is that the mass of the metal element source is 535 g, wherein the metal element source is TiO2, ZrO2, SnO2, GeO2 and HfO2 in a molar ratio of 1:1:1:1:1.
[0077] Example 3
[0078] The difference from Example 1 is that the mass of the metal element source is 610.46 g, wherein the metal element source is CeO2, ZrO2, GeO2 and HfO2 in a molar ratio of 1:1:1:1.
[0079] Example 4
[0080] The difference from Example 1 is that a liquid phase method is used to prepare a lithium ion solid phase electrolyte, including mixing zirconium nitrate, lead nitrate and cerium nitrate in a molar ratio of 1:1:1 with 500 ml of water to form a first metal element source solution, and dissolving 22.8 g of titanium ethoxide in 200 ml of ethanol to form a second metal element source solution;
[0081] Add 14.5 g of lithium source (Li2CO3) and 69 g of phosphorus source (NH4H2PO4) to 200 ml of water to form a lithium source-phosphorus source mixed solution, mix the first metal element source solution, the second metal element source solution and the lithium source-phosphorus source mixed solution, stir for 3 hours, dry at 120°C, and sinter at 800°C in an oxygen atmosphere to obtain a NASICON type lithium ion solid electrolyte.
[0082] Example 5
[0083] The difference from Example 1 is that the solid content of the coating slurry is 40%.
[0084] Example 6
[0085] The difference from Example 1 is that the mass of the metal element source is 444.66 g, wherein the metal element source is TiO2, ZrO2, SnO2, GeO2 and HfO2 in a molar ratio of 5:2:1:1:1.
[0086] Comparative Example 1
[0087] The difference from Example 1 is that 10.14 g of Li2CO3, 3.06 g of Al2O3, 13.6 g of TiO2, and 34.5 g of NH4H2PO4 are ball-milled in isopropanol for 5 h and sintered at 900°C for 2 h in an air atmosphere to obtain a NASICON type lithium-ion solid electrolyte.
[0088] Comparative Example 2
[0089] The difference from Example 1 is that 10.14 g of Li2CO3, 16 g of TiO2, and 34.5 g of NH4H2PO4 are ball-milled in isopropanol for 5 h and sintered at 900°C for 2 h in an air atmosphere to obtain a NASICON type lithium ion solid electrolyte.
[0090] Comparative Example 3
[0091] The difference from Example 1 is that HfO2 is not included.
[0092] Performance Testing
[0093] The NASICON lithium-ion solid electrolytes prepared in the above Examples 1-4 and Comparative Examples 1-2 were subjected to X-ray diffraction testing. The testing process was as follows: using a Cu target, a voltage of 40 kV, a current of 40 mA, a 2θ angle range of 10°-80°, and a step size of 0.066° / s. Figure 3 The X-ray diffraction spectra of the NASICON-type lithium-ion solid electrolytes prepared in Examples 1-4 and Comparative Examples 1-2 of the present application show that the present application can prepare a NASICON-type lithium-ion solid electrolyte.
[0094] The NASICON lithium ion solid electrolytes prepared in the above Examples 1-6 and Comparative Examples 1-3 were subjected to a water absorption test. The test process was as follows: 0.1 g of the NASICON lithium ion solid electrolyte was exposed to a -10°C dew point environment for 24 hours, and a coulometric moisture meter was used. The test conditions were a temperature of 160°C and a time of 600 seconds to obtain its water content. The test results are shown in Table 1.
[0095] The NASICON lithium ion solid electrolytes prepared in the above-mentioned Examples 1-6 and Comparative Examples 1-3 were subjected to ion conductivity tests. The test process was as follows: 0.5 g of NASICON lithium ion solid electrolyte powder was taken, pressed into a disc with a diameter of 12 mm, and sintered at 800°C in an air atmosphere. After the disc was taken out, the round surfaces at both ends were sprayed with gold, sandwiched between two stainless steel sheets, and an electrochemical impedance spectroscopy test was performed in a CR2032 button battery. The test frequency range was 5 MHz-1 Hz. In the obtained impedance spectrum, there was an arc in the high frequency region, and the diameter of the arc was used as the R value for ion conductivity calculation. The ion conductivity was calculated using the following formula: σ = L / (R·A), where L is the thickness of the solid electrolyte sheet (cm), and A is the end surface area of the solid electrolyte sheet (cm 2 ), R is the diameter of the high-frequency arc segment in the impedance spectrum (Ω). The test results are shown in Table 1. Figure 4 This is the electrochemical impedance spectrum of the NASICON lithium ion solid electrolyte sheet prepared in Example 1 of the present application. It can be seen that there is an arc position (arrow direction) in the high frequency region, and the arc diameter is used as the R value for ion conductivity calculation.
[0096] The NASICON lithium ion solid electrolytes prepared in the above Examples 1-6 and Comparative Examples 1-3 were tested for lithium dissolution. The test process was as follows: 3 g of crushed powder was placed in 120 mL of deionized water and stirred for 2 h. The filtrate was filtered through a filter membrane and then subjected to ICP-AES test. The test results are shown in Table 1.
[0097] The membranes prepared in the above-mentioned embodiments 1-6 and comparative examples 1-3 were subjected to a water absorption test. The test process was as follows: 0.1 g of the membrane to be tested was taken and exposed to a dew point environment of -20°C for 48 hours. A coulometric moisture meter was used, and then a moisture test was performed. The test conditions were a temperature of 150°C and a time of 300 seconds to obtain the moisture content of the membrane; after the membrane was baked at 95°C for 24 hours, a coulometric moisture meter was used, and then a moisture test was performed. The test conditions were a temperature of 150°C and a time of 300 seconds to obtain the moisture content after baking at 95°C for 24 hours; after the membrane was baked at 95°C for 96 hours, a coulometric moisture meter was used, and then a moisture test was performed. The test conditions were a temperature of 150°C and a time of 300 seconds to obtain the moisture content after baking at 95°C for 96 hours; the test results are shown in Table 2.
[0098] The diaphragms prepared in the above Examples 1-6 and Comparative Examples 1-3 were subjected to ion conductivity tests according to GB / T 36363-2018, using LiPF6 with a lithium salt concentration of 1M and an electrolyte solution of EC, DMC, and DEC in a volume ratio of 1:1:1. The test results are shown in Table 2.
[0099] The batteries prepared in the above-mentioned Examples 1-6 and Comparative Examples 1-3 were subjected to Hipot (dielectric withstand voltage performance) test. The test process is as follows: the leakage current and voltage drop generated by the battery under the test high voltage output by the high-voltage machine are compared with the set value to determine whether the electronic insulation performance of the battery is strong enough and whether there are defects. By testing 20 identical batteries, the pass rate after the test is calculated; the set pulse voltage is 200V. Because of solvent residue and high electronic conductivity, there are three common errors caused by high voltage. (1) Before reaching the set voltage V, the voltage drop at a certain time is very large, reaching the system designed Vx (100V) or more; (2) Before reaching the set voltage V, the voltage drop is greater than the set voltage V1=10V; (3) After reaching the set voltage V, the voltage drop is greater than the set voltage V2=40V. The above three errors are recorded as Hipot test failure. For batteries that fail the Hipot test, they will be vacuum-baked at 95℃ for 24h and then undergo Hipot test again. The results are shown in Table 3.
[0100] The batteries prepared in the above Examples 1-6 and Comparative Examples 1-3 were subjected to rate and cycle performance tests. The test process was as follows: charge and discharge for 3 cycles at 0.33C, taking the discharge capacity of the last cycle as C, and then conducting rate and cycle tests. Capacity tests were conducted at 0.1C and 3C rates, and the capacity retention rate was obtained after 300 cycles at 1C rate. The test results are shown in Table 3.
[0101] Table 1 Test results of NASICON lithium-ion solid electrolyte
[0102]
[0103] Table 2 Test results of diaphragm
[0104]
[0105] Table 3 Battery test results
[0106]
[0107] According to Examples 1-6 and Comparative Examples 1-3, it can be seen that the NASICON lithium ion solid electrolyte and diaphragm provided by the present application have low hydrophilicity, low water content, high ionic conductivity, good structural stability, and the obtained battery has good rate performance, excellent cycle performance, high Hipot pass rate, low preparation cost, and is conducive to the industrial application of the battery. According to Examples 1 and 2-5, it can be seen that suitable metal elements, suitable metal element molar ratios, and suitable preparation methods are all conducive to improving the ionic conductivity of the NASICON lithium ion solid electrolyte and diaphragm and reducing its water content; According to Example 1 and Comparative Example 1, it can be seen that the NASICON lithium ion solid electrolyte provided by the present application has low water content, high ionic conductivity, and low lithium dissolution, indicating that it has high structural stability and is not easy to decompose; According to Example 1 and Comparative Example 2, it can be seen that the NASICON lithium ion solid electrolyte and diaphragm provided by the present application have both high ionic conductivity and low water absorption, which is conducive to improving the electrochemical performance of the battery.
[0108] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. A diaphragm, characterized in that: The diaphragm includes a base film and a coating layer arranged on at least one side of the base film, the coating layer includes a NASICON type lithium ion solid electrolyte, the chemical formula of the NASICON type lithium ion solid electrolyte is LiM2(PO4)3, and M is at least four tetravalent metal elements.
2. The diaphragm according to claim 1, characterized in that The metal element is selected from Ti, Ge, Mn, In, Te, Sc, Y, V, Cr, Hf, Ce, Zr, Pb and Sn.
3. The diaphragm according to claim 1, characterized in that Among the at least four tetravalent metal elements, the molar percentage of each of the metal elements is greater than or equal to 10%.
4. The diaphragm according to any one of claims 1 to 2, characterized in that: The metal elements are Ti, Ge, Sn, Zr and Hf.
5. The diaphragm according to claim 4, characterized in that The chemical formula of the NASICON type lithium ion solid electrolyte includes LiTi 0.4 Zr 0.4 Hf 0.4 Sn 0.4 Ge 0.4 (PO4)3、LiTi 0.8 Hf 0.4 Sn 0.4 Ge 0.4 (PO4)3、LiCe 0.5 Zr 0.4 Ge 0.5 Hf 0.5 (PO4)3、LiTi 0.5 Zr 0.5 Pb 0.5 Ce 0.5 (PO4)3 and LiTi 1.4 Hf 0.2 Sn 0.2 Ge 0.2 (PO4)3 or more.
6. The diaphragm according to claim 1, characterized in that The configuration entropy of the NASICON lithium-ion solid electrolyte is greater than or equal to 10.73 J / (mol·K).
7. The diaphragm according to claim 1, characterized in that The D50 particle size of the NASICON type lithium ion solid electrolyte is greater than or equal to the pore size of the base membrane; The D50 particle size of the NASICON type lithium ion solid electrolyte is 0.5 μm-1.5 μm, and the pore size of the base membrane is 0.7 μm-1.2 μm.
8. The diaphragm according to claim 1, characterized in that The base film has a thickness of 7 μm-20 μm, and the coating layer has a thickness of 0.5 μm-5 μm.
9. The diaphragm according to claim 1, characterized in that The ionic conductivity of the NASICON type lithium ion solid electrolyte is greater than or equal to 0.1 mS / cm, and the water absorption per gram of the NASICON type lithium ion solid electrolyte is less than or equal to 0.2 wt %.
10. The diaphragm according to claim 1, characterized in that The ion conductivity of the membrane is greater than or equal to 0.9 mS / cm, and the water absorption per gram of the membrane is less than or equal to 0.19 wt %.
11. A method for preparing a diaphragm according to any one of claims 1 to 10, characterized in that: include: The metal element source, the lithium source and the phosphorus source are mixed and sintered to obtain a NASICON type lithium ion solid electrolyte; The NASICON type lithium ion solid electrolyte is mixed with a solvent to obtain a coating slurry, and the coating slurry is disposed on at least one side of a base film to form a coating layer to obtain a separator.
12. The preparation method according to claim 11, characterized in that: The molar ratio of the lithium element in the lithium source, the phosphorus element in the phosphorus source and the metal element in the metal element source is (0.33-0.5):(1.4-1.6):
1.
13. The preparation method according to claim 11, characterized in that: The metal element source includes one or more of metal nitrates, metal organic salts and metal oxides.
14. The preparation method according to claim 11, characterized in that: The solid content of the coating slurry is 20%-40%, and the sintering temperature is 700°C-1000°C.
15. A battery, characterized in that: The battery comprises the diaphragm according to any one of claims 1 to 10 or the diaphragm prepared by the preparation method according to any one of claims 11 to 14.
16. An electrical equipment, characterized in that: The electrical device comprises the battery according to claim 15.